By knowledge & by love : charity and knowledge in the moral theology of St. Thomas Aquinas - Sherwin, Michael S., 1963- (Book collections on Project MUSE., 2005)
"By Knowledge and By Love represents a major contribution to Thomistic moral theology and philosophy by providing a thoughtful examination of Aquinas' psychology of action and his theology of charity. Through a comprehensive analysis of the relation between intellect and will, knowledge and love, and charity and the infused intellectual virtues, Sherwin concludes that, far from divorcing the will from reason, Aquinas in his later works integrates reason and will more closely together."--Jacket.